Theory-of-mind in individuals with Alström syndrome is related to executive functions, and verbal ability - Frölander, Hans-Erik (Front Psychol, 2015)
Objective: This study focuses on cognitive prerequisites for the development of theory-of-mind (ToM), the ability to impute mental states to self and others in young adults with Alström syndrome (AS). AS is a rare and quite recently described recessively inherited ciliopathic disorder which causes progressive sensorineural hearing loss and juvenile blindness, as well as many other organ dysfunctions. Two cognitive abilities were considered; Phonological working memory (WM) and executive functions (EF), both of importance in speech development. Methods: Ten individuals (18–37 years) diagnosed with AS, and 20 individuals with no known impairment matched for age, gender, and educational level participated. Sensory functions were measured. Information about motor functions and communicative skills was obtained from responses to a questionnaire. ToM was assessed using Happés strange stories, verbal ability by a vocabulary test, phonological WM by means of an auditory presented non-word serial recall task and EF by tests of updating and inhibition. Results: The AS group performed at a significantly lower level than the control group in both the ToM task and the EF tasks. A significant correlation was observed between recall of non-words and EF in the AS group. Updating, but not inhibition, correlated significantly with verbal ability, whereas both updating and inhibition were significantly related to the ability to initiate and sustain communication. Poorer performance in the ToM and EF tasks were related to language perseverance and motor mannerisms. Conclusion: The AS group displayed a delayed ToM as well as reduced phonological WM, EF, and verbal ability. A significant association between ToM and EF, suggests a compensatory role of EF. This association may reflect the importance of EF to perceive and process input from the social environment when the social interaction is challenged by dual sensory loss. We argue that limitations in EF capacity in individuals with AS, to some extent, may be related to early blindness and progressive hearing loss, but maybe also to gene specific abnormalities.